2015
DOI: 10.1124/jpet.115.224832
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Efficacy of Targeted Pulmonary Delivery of a Protein Kinase C-δ Inhibitory Peptide: Impact on Indirect Lung Injury

Abstract: Sepsis and sepsis-induced lung injury remain a leading cause of death in intensive care units. We identified protein kinase C-d (PKCd) as a critical regulator of the acute inflammatory response and demonstrated that PKCd inhibition was lung-protective in a rodent sepsis model, suggesting that targeting PKCd is a potential strategy for preserving pulmonary function in the setting of indirect lung injury. In this study, whole-body organ biodistribution and pulmonary cellular distribution of a transactivator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 73 publications
4
39
0
Order By: Relevance
“…Previously, our group has introduced a novel therapeutic paradigm that uses a peptide antagonist to inhibit selectively PKCd activity and neutrophilendothelial interactions to protect vascular endothelial integrity and attenuate sepsis-induced tissue damage [6][7][8]. The role of PKCd in rodent sepsis models and in neutrophils or endothelial is shown to be stimulus dependent and organ specific [7,8,36,37]. The role of PKCd in rodent sepsis models and in neutrophils or endothelial is shown to be stimulus dependent and organ specific [7,8,36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our group has introduced a novel therapeutic paradigm that uses a peptide antagonist to inhibit selectively PKCd activity and neutrophilendothelial interactions to protect vascular endothelial integrity and attenuate sepsis-induced tissue damage [6][7][8]. The role of PKCd in rodent sepsis models and in neutrophils or endothelial is shown to be stimulus dependent and organ specific [7,8,36,37]. The role of PKCd in rodent sepsis models and in neutrophils or endothelial is shown to be stimulus dependent and organ specific [7,8,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…A key step in neutrophil-mediated tissue damage is the migration of activated neutrophils across the vascular endothelium [4,5]. Our previous studies indicated a role for PKCd in regulating neutrophil migration but did not address specific mechanisms or identify specific steps by which PKCd impacts the interaction of neutrophils and endothelial cells during inflammation [6][7][8]. Our previous studies indicated a role for PKCd in regulating neutrophil migration but did not address specific mechanisms or identify specific steps by which PKCd impacts the interaction of neutrophils and endothelial cells during inflammation [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use bMFA to investigate whether mouse neutrophil‐endothelial cell interactions and microvascular endothelium barrier characteristics, as well as response to a novel anti‐inflammatory agent, are predictive of human cell responses. Previously, we demonstrated that protein kinase C‐delta (PKCδ) is an important regulator of neutrophil‐endothelial cells interaction during inflammation and that a PKCδ‐TAT peptide inhibitor (PKCδ‐ i ) may serve as a potential novel anti‐inflammatory therapeutic . In this study, we tested the hypothesis that mouse and human cells do not respond similarly to activation and investigated whether the response of mouse cells to an anti‐inflammatory agent is likely to provide data that would be predictive of its efficacy in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis was induced by the cecal ligation and puncture (CLP) method as described previously . Sham controls underwent a laparotomy without cecal ligation or puncture.…”
Section: Methodsmentioning
confidence: 99%
“…At 24 post‐surgery, rats were euthanized and the lungs were gravity‐fixed with 10% neutral buffered formalin instillation into the airways; the trachea was then tied off to maintain inflation during fixation. After fixation, lungs were paraffin‐embedded, sectioned (5‐10 μm thick), and stained with hematoxylin‐eosin (H&E) as we described previously …”
Section: Methodsmentioning
confidence: 99%